PROMOWANIE EDUKACJI A ROZWÓJ JEJ ZAPLECZA INFORMACYJNEGO - Januszkiewicz, Franciszek (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
The following issues are discussed in the article: modern education directed towards the future; multimedia education; conditions for more efficient continuous education; educational professionalism and school administration; informational environment of education. The author proposes and designs the creation of National Center of Continuous Education (NCEU).
Keywords: Informacja; Multimedia; Edukacja; Polityka edukacyjna; Kształcenie multimedialne; Pakiety dydaktyczne; Information; Education; Educational politics; Multimedia education; Neodidagmata